Mengenali Beberapa Faktor Perubahan Yang Terjadi Pada TK Ashabul Kahfi - Afifah Nurhajjah; Gina Puspita Ayu; Luthfia Daffa; Ramdani Bayu Putra (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Recognize the changes that occur in an agency with several factors that occur, namely those located at the Ashabul Kahfi Foundation, Jalan Kolam Indah IV, Mata Air, Kec. South Padang, Padang City, West Sumatra. By using a change management scheme, we got the results from the problem basic learning (PBL) that we carried out, there are several implications for the Ashabul Kahfi Padang Kindergarten, the challenge of human resource (teacher) readiness as the main pillar of implementing the independent curriculum. The existence of teachers in implementing the independent curriculum is a locomotive and driving force for the success of various independent learning programs such as differentiated learning, implementing projects to strengthen Pancasila student profiles and learning assessments as well as empowering technology as a learning support tool. Therefore, strengthening the existence of teachers through development programs according to needs needs to be carried out continuously and consistently, especially if you look at the results of teacher professional development programs so far that have not had a significant impact on improving quality.